2009
DOI: 10.1089/neu.2009.0959
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Overexpressing Tissue Inhibitor of Metalloproteinase TIMP-1

Abstract: Accumulating data suggest that matrix metalloproteinases (MMPs) may be important mediators in the pathophysiology of acute brain injury after trauma or stroke. Here, we test the hypothesis that the endogenous tissue inhibitor of metalloproteinase (TIMP-1) is neuroprotective in vitro and in vivo. For in vitro studies, primary cortical neuronal cultures were subjected to hypoxia and reoxygenation. Treatment with recombinant TIMP-1 protein significantly decreased neuronal death. In vivo studies in models of brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
57
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 48 publications
5
57
0
2
Order By: Relevance
“…In vitro and in vivo models of brain trauma and stroke suggest that TIMP1 is neuroprotective and that overexpression of TIMP1 prevents the BBB leakage and reduces neuronal cell death. 50 Downregulation of TIMP1 was observed in HIV-infected macrophages and vascular endothelial cells. 51 In our previous studies, among different dysregulated genes, TIMP1 was one of the highly downregulated synaptic plasticity genes in HIV-infected neuronal cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In vitro and in vivo models of brain trauma and stroke suggest that TIMP1 is neuroprotective and that overexpression of TIMP1 prevents the BBB leakage and reduces neuronal cell death. 50 Downregulation of TIMP1 was observed in HIV-infected macrophages and vascular endothelial cells. 51 In our previous studies, among different dysregulated genes, TIMP1 was one of the highly downregulated synaptic plasticity genes in HIV-infected neuronal cells.…”
Section: Discussionmentioning
confidence: 98%
“…[53][54][55] TIMP1 has been reported to have neuroprotective effects equivalent to that of brain-derived neurotropic factor. 50 Therefore, supplementing TIMP1 may …”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 also has long-term beneficial effects on neurovascular remodeling and behavioral recovery after stroke in adult rats (8,9). In the adult rat central nervous system, elevated TIMP-1 expression levels may play a neuroprotective role after kainate-induced excitotoxic seizures (10), and gene transfer of TIMP-1 and 2 protects against global cerebral ischemia in mice (11,12). The fact that MMPs and TIMPs are secreted proteins that can easily be measured in bodily fluids including peripheral blood (13) highlights their potential as biomarkers for brain injury.…”
mentioning
confidence: 99%
“…Indeed, we have shown that overexpression of TIMP-1 results in suppression of the MMP-3 activity increase and provides cell protection in CATH.a cells exposed to BFA. Protective roles of TIMP-1 have previously been reported in other systems (35)(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 68%